HYGIENIC ASSESSMENT OF MICROCLIMATE INDICATORS OF SPINNING PRODUCTION - Nuraliyev Firdavs Nekkadamovich; Otashexov Zokir Ismoilovich (Journal Park Publishing, 2025)
In order to minimize the adverse impact of working conditions on workers in the spinning industry, the labor protection and safety services of the spinning industries, under the supervision of the bodies of the committee for sanitary and epidemiological welfare and public health, must implement a set of measures to improve (or optimize) working conditions. According to Sanitary Rules and Norms №0324-16, the air temperature in workplaces during the warm period of the year should not exceed 31°C with a relative humidity of no more than 55% and a mobility of 0.3 - 0.5 m / sec. To protect the body of workers from unfavorable microclimatic indicators (excess heat, low levels of RHV), spinning shops must be equipped with modern climate control mechanisms for regulating the temperature and humidity conditions.
Keywords: Microclimate indicators, spinning production, working conditions, occupational hygiene.